Chlamydia trachomatis Requires Functional Host-Cell Mitochondria and NADPH Oxidase 4/p38MAPK Signaling for Growth in Normoxia - Thapa, Jeewan; Yoshiiri, Gen; Ito, Koki; Okubo, Torahiko; Nakamura, Shinji; Furuta, Yoshikazu; Higashi, Hideaki; Yamaguchi, Hiroyuki (Frontiers in Cellular and Infection Microbiology, 2022)
Chlamydia trachomatis (Ct) is an intracellular energy-parasitic bacterium that requires ATP derived from infected cells for its growth. Meanwhile, depending on the O2 concentration, the host cells change their mode of ATP production between oxidative phosphorylation in mitochondria (Mt) and glycolysis; this change depends on signaling via reactive oxygen species (ROS) produced by NADPH oxidases (NOXs) as well as Mt. It has been proposed that Ct correspondingly switches its source of acquisition of ATP between host-cell Mt and glycolysis, but this has not been verified experimentally. In the present study, we assessed the roles of host-cell NOXs and Mt in the intracellular growth of CtL2 (L2 434/Bu) under normoxia (21% O2) and hypoxia (2% O2) by using several inhibitors of NOXs (or the downstream molecule) and Mt-dysfunctional (Mtd) HEp-2 cells. Under normoxia, diphenyleneiodonium, an inhibitor of ROS diffusion, abolished the growth of CtL2 and other Chlamydiae (CtD and C. pneumoniae). Both ML171 (a pan-NOX inhibitor) and GLX351322 (a NOX4-specific inhibitor) impaired the growth of CtL2 under normoxia, but not hypoxia. NOX4-knockdown cells diminished the bacterial growth. SB203580, an inhibitor of the NOX4-downstream molecule p38MAPK, also inhibited the growth of CtL2 under normoxia but not hypoxia. Furthermore, CtL2 failed to grow in Mtd cells under normoxia, but no effect was observed under hypoxia. We conclude that under normoxia, Ct requires functional Mt in its host cells as an ATP source, and that this process requires NOX4/p38MAPK signaling in the host cells. In contrast to hypoxia, crosstalk between NOX4 and Mt via p38MAPK may be crucial for the growth of Ct under normoxia.